PELAKSANAAN KLAIM ASURANSI JIWA PT. PRUDENTIAL LIFE ASSURANCE/PRU AINI PEMATANG SIANTAR TERKAIT BATAS WAKTU PENGAJUAN KLAIM - Moria Lastina; Mardalena Hanifah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Insurance is an agreement by which binding to the insured to receive a premium to provide reimbursement to him for the loss, damage or loss that might be expected clappers suffered as a result of a evenemen (events not sure). One thing is quite complicated insurance claims is a matter which is the money the insurance provided by an insurance company or insurer to the insured.This type of research can be classified in this type of juridical sociological research, namely the legal research that discusses the legal identification and effectiveness law. This research was conducted at PT. Prudential Life Assurance / Pru Aini Siantar, while the sample population is overall the parties relating to the issues researched in this study, the source of the data used are primary data and secondary data, methods of collecting data in this study with interviews and literature study.From the research there are three main issues that can be inferred. First, the implementation of life insurance agreement PT Prudential Life Assurance / Pru Aini Siantar with the insured has not been fully implemented. Evidently, there are many insured who received a late claim, do not understand do not even understand about the claim, there are still many requirements that are less claims and not in accordance with the procedure. This proves the persistence of the things in the agreement contained in a life insurance policy that has not been done. Second, barriers that occur in the life insurance agreement with PT Prudential Life Assurance / Pru Aini Siantar are insured are often late paying premiums to a life insurance agent, a lack of public knowledge about life insurance, so that delays in the implementation of insurance between the PT Prudential Life Assurance / Pru Aini Siantar with the insured person. Third, the efforts made by PT Prudential Life Assurance / Pru Aini Siantar against obstacles that arise are giving off facilities premiums (premium holiday) to the insured in order to keep the policy agreements materialize and provide accurate information about the life insurance contract to the insured. Suggestions Writer, first, to implement the provisions of the claim that is not beyond the deadline. Second, find out more information life insurance agreement. Third, reinforce the legislation by including sanctionsKeywords: Life Insurance-Claim-PT Prudential Life Assurance